2020
DOI: 10.1371/journal.pone.0227447
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to particulate matter from air pollution in the outdoor workplaces in Almaty during the cold season

Abstract: Background A large fraction of population in Almaty and other Kazakhstan cities is employed in the outdoor jobs and likely exposed to high levels of particulate matter (PM) during the cold season. The magnitude of such occupational exposure remains unknown; therefore, the aim was to quantify the levels of exposure to PM 10 in the outdoor workplaces in Almaty in order to guide future interventions of primary prevention. Methods Outdoor security non-smoking guards (N = 12) wore TSI DustTrack AM520 aerosol monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…These numbers, however, do not consider some exposure to particulate matter (PM) in the workplaces, not traditionally considered hazardous, but shown to have high concentrations of pollutants. A recent study in Almaty ( 5 ) has demonstrated extremely high levels of PM 10 in winter in Almaty from fossil fuel burning for heating and cooking either by households in the city and in the suburbs or central heating plants in the city. Such significant exposure has serious implications with regard to whom to consider an exposed population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These numbers, however, do not consider some exposure to particulate matter (PM) in the workplaces, not traditionally considered hazardous, but shown to have high concentrations of pollutants. A recent study in Almaty ( 5 ) has demonstrated extremely high levels of PM 10 in winter in Almaty from fossil fuel burning for heating and cooking either by households in the city and in the suburbs or central heating plants in the city. Such significant exposure has serious implications with regard to whom to consider an exposed population.…”
Section: Discussionmentioning
confidence: 99%
“…These countries are known to have had high level of industrialization prior to recent transition period with high ratio of population exposed to VGDF in the industry. In addition, current levels of air pollution in these countries are worrisome ( 4 , 5 ), adding to high expected prevalence of COPD, but no studies from the region have been systematically summarized in the English literature.…”
Section: Introductionmentioning
confidence: 99%
“…Almaty is a city with high reported levels of air pollution, whereas the exposure to combustion products from fossil fuel use for heating and cooking from the suburb and heating plants in winter may be high [ 18 ]. Ambient air pollution may result in higher exhaled CO levels in those living in highly polluted cities [ 19 ]; however, the contribution of ambient CO in our cohort was negligible compared to cigarette smoking and waterpipe use because among 452 non-current smokers and never-waterpipe users, 180 (40%) had exhaled CO 0, 1 or 2 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…Adjustable tubes were connected to both the samplers and placed near to the breathing zone of the individual. This approach is frequently employed to understand occupational exposure of air pollutants [24,25]. A total of 8 hours of exposure measurement representing the active working period was collected.…”
Section: Measurements Of Ambient Pm25 and Personal Exposurementioning
confidence: 99%